(untitled) (Sains Humanika, 2018)
This study is aimed at obtaining and gathering information on the background of teachers who teach at tahfiz private institutions throughout the state of Selangor regarding their age, education level, origin, status of post, teaching experience, salary or monthly allowance they received the virtues they earn. The study was quantitative in which a total of 90 questionnaires were distributed to respondents. Of this total, only 86 forms were returned and analyzed Quantitative data was analyzed descriptively using Statistical Package for Social Science (SPSS) version 14.0. It is hoped that the findings of this study will be given due attention by the authorities in the state of Selangor, in order to improve the quality of tahfiz education in the state, as any problems faced by these teachers will indirectly lead to a negative impact on the teaching and learning process which they control.